Championing science : communicating your ideas to decision makers - Aines, Roger D., 1958-; Aines, Amy L., 1956- (University of California Press, 2019)
"Championing Science is a comprehensive guide that helps scientists persuasively communicate complex scientific ideas to decision makers in government, policy, and education. The book provides real-world tactics for scientists to help build vital communication, influence, and emotional intelligence skills that motivate decision makers, with little to no science background, to understand and support their science. Through instruction, interviews, and examples, scientists learn why inspiring decision makers to act requires extracting the essence of scientific findings, crafting understandable messages, simplifying visuals, bridging paradigm gaps, and storytelling. Principles for championing science come to life through stories of science champions such as Robert Millikan, Vannevar Bush, the work between Caltech and MIT, and others. With Championing Science, scientists will effectively learn how to use their communication skills to garner funding, secure future research, and, ultimately, impact policy"--Provided by publisher.